SOIL DISTRIBUTION IN STRUMICA RIVER BASIN AND ITS IMPORTANCE FOR AGRICULTURAL PRODUCTION - Mile MARKOSKI, Tatjana MITKOVA, Vjekoslav TANASKOVIK, and Velibor SPALEVIC (Agriculture & Forestry, Vol. 64 Issue 4: 121-128, 2018, 2018)
This paper is a result of many years of field and laboratory research of the soils in Strumica river basin, spread out on 148.124,02 ha, ranging from 150 to 1540 m above the sea level in order to gain a better understanding of the productive capacities of the soils and measures for their improvement. The filed research of the soils has been done according to methods described by (Markoski et al., 2014). In laboratory, the following analyses have been carried out on the soil samples: hygroscopic moisture; mechanical composition; pH of the soil solution; humus content and total nitrogen; content of carbonates; available nutrients P2O5 and K2O. The mechanical composition and chemical properties of the soils have been determined by standard methods described by (Belić et al, 2014), (Mitrikeski & Mitkova, 2001); (Resulović et al., 1971), (Džamić et al., 1996). This area is very heterogeneous, with numerous relief forms, with different expositions and inclinations, and with great differences of altitude. Additionally, there are several geological formations of a very heterogeneous petrographic-mineralogical composition and climate-vegetation zones. Long-term effects from human involvement should also be noted. The vast diversity of the factors required for soil formation in this area is the reason for the formation of many different soil types as well as the lower taxonomic units. These types of soils are characterized by different properties (chemical,physical, and physical-mechanical, productive). Therefore, they have varied effects on agricultural production. There are 14 (fourteen) different soil types distributed in the Strumica river basin together with a considerable amount of subtypes, varieties and forms. Mountain soils are prevalent in this river basin: 79.337,6 ha, or (53.56%) of the whole. Soils of lake terraces and of undulated hilly relief cover 30.507,42 ha,(20.59%), whereas soils of colluvial fans occupy 18.739,6 ha (12.65%) of the area. Finally, soils of the plains occupy 17.784,4 ha (12.01%) and Urbisol 1.755,57 ha (1.18%).
Keywords: soil types, Strumica river basin